Theses and Dissertations from ULisboa to the world: a case study on the international visibility of academic publications in the institutional repositories of the University of Lisbon - Melo, Luiza Baptista (2021)
Focused on the collection of theses and dissertations, the aim of the following study is tolook to the scientific production of ULisboa and analyse the international visibility of it through the statistical report of these two institutional repositories for the last 10 years (2010-2019). For this purpose, the total number of thesis and dissertations of the ULisboa, archived in both repositories, were collected, for the period 2010-2019 (10 years of implementation of the institutional repositories). Usage statistics (views and downloads) were obtained as well as the home countries of these accesses. A descriptive analysis was performed. Results showed that the number of thesis and dissertation archived in the repositories has been growing, as well as their use (views and downloads) is very significant in both repositories.